L’OPÉRA JONAS D’ANATOL VIERU. 1. SYMBOLES ET INTERPRÉTATIONS POLITIQUES - STAN, Luana (Studia Universitatis Babes-Bolyai Musica, 2010)
The aim of this text is to analyse the opera Jonas (1976) of the Romanian composer Anatol Vieru. The first part is concentrated on the interpretations of the literary and musical symbols of this opera in the communist political context. The second part is analysing the specific structures and the symmetries (palindromes).